(untitled) (Journal of Humanitarian and Applied Sciences, 2024)
Praise be to Allah, and prayers and peace be upon the Messenger of God, his family, his companions, and those who follow him. as for what follows: Judge Abd al-Wahhab al-Baghdadi - may God have mercy on him - had a great interest in mentioning the narrations in which there was disagreement from the imam of the Maliki school of thought, Malik on the authority of Anas - may God have mercy on him - and I am not more degraded for that than his mention of it in his book (Al-Ma’ounah Ali Madhab Alam Al-Madinah), which is The subject of the study of the issues in this research, and the judge often referred to these narrations by saying (and from him on the issue there are two narrations). (And from him there are three narrations), and the main goal of collecting these narrations and studying the issues related to them is “to ensure the accuracy of their attribution to the imam of the school of thought, and to know the reckless statements of the school of thought that are based on one of these narrations.” I have limited this research to collecting and studying the narrations and issues related to them. The Book of Purity from the aforementioned book.